2018
DOI: 10.1093/mnras/sty1126
|View full text |Cite
|
Sign up to set email alerts
|

KIC 3240411 – the hottest known SPB star with the asymptotic g–mode period spacing

Abstract: We report the discovery of the hottest hybrid B-type pulsator, KIC 3240411, that exhibits the period spacing in the low-frequency range. This pattern is associated with asymptotic properties of high-order gravity (g-) modes. Our seismic modelling made simultaneously with the mode identification shows that dipole axisymmetric modes best fit the observations. Evolutionary models are computed with MESA code and pulsational models with the linear non-adiabatic code employing the traditional approximation to includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 51 publications
2
99
1
1
Order By: Relevance
“…Since the end of the nominal 4-years Kepler mission, the extremely high precision light curves have been used to discover and analyse rotationallysplit modes and period spacing patterns of prograde dipole g modes in dozens of SPB stars (Pápics et al, 2014(Pápics et al, , 2015(Pápics et al, , 2017. Such asteroseismic studies have revealed the interior rotation rates, convective core overshooting and mixing in main-sequence B stars (Moravveji et al, 2015(Moravveji et al, , 2016Szewczuk and Daszyńska-Daszkiewicz, 2018). Despite massive stars not being included in the Kepler field of view, ingenious techniques to extract the light curves of nearby massive stars have been successful (Pope et al, 2016(Pope et al, , 2019a, which includes the scattered-light variability of the O9.5 Iab star HD 188209 (Aerts et al, 2017).…”
Section: The Kepler and K2 Missionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the end of the nominal 4-years Kepler mission, the extremely high precision light curves have been used to discover and analyse rotationallysplit modes and period spacing patterns of prograde dipole g modes in dozens of SPB stars (Pápics et al, 2014(Pápics et al, , 2015(Pápics et al, , 2017. Such asteroseismic studies have revealed the interior rotation rates, convective core overshooting and mixing in main-sequence B stars (Moravveji et al, 2015(Moravveji et al, , 2016Szewczuk and Daszyńska-Daszkiewicz, 2018). Despite massive stars not being included in the Kepler field of view, ingenious techniques to extract the light curves of nearby massive stars have been successful (Pope et al, 2016(Pope et al, , 2019a, which includes the scattered-light variability of the O9.5 Iab star HD 188209 (Aerts et al, 2017).…”
Section: The Kepler and K2 Missionsmentioning
confidence: 99%
“…KIC 3240411 was found to be a relatively young star near the zero-age main sequence with the upper limit on its convective core overshooting being f ov ≤ 0.030. The best-fitting model parameters (i.e., model #2 in Table 2 of Szewczuk and Daszyńska-Daszkiewicz, 2018) are included in Table 1. Importantly, Szewczuk and Daszyńska-Daszkiewicz (2018) also studied the effect of rotation and opacity data within their modeling for the purposes of explaining mode excitation of high-radial order g modes in such stars.…”
Section: Space-based Studiesmentioning
confidence: 99%
“…Secure mode identification had to await nearly unin-Contact: joey.mombarg@kuleuven.be terrupted time series photometry with at least a factor ten longer time base, such as that assembled with the Kepler space telescope (Borucki et al 2010). Meanwhile, lots of progress has been made on the observational side in this topic over the past few years with firm detections of period spacing patterns reported in Pápics et al (2014Pápics et al ( , 2015; Kurtz et al (2014); Saio et al (2015); Van Reeth et al (2015a); Schmid et al (2015); Van Reeth et al (2016); Murphy et al (2016); Guo et al (2016); Ouazzani et al (2017); Saio et al (2017Saio et al ( , 2018; Szewczuk & Daszyńska-Daszkiewicz (2018) and Li et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical interpretation has been used to interpret period spacing patterns detected in space photometry in terms of near-core rotation, overshooting, and diffusive envelope mixing (Van Reeth et al 2016;Moravveji et al 2015Moravveji et al , 2016Schmid & Aerts 2016;Ouazzani et al 2017;Pápics et al 2017). Recently, period-spacing patterns have been modelled to reveal the shape and extent of core overshooting in a handful of SPB and γ Dor stars (Moravveji et al 2015(Moravveji et al , 2016Schmid & Aerts 2016;Buysschaert et al 2018;Szewczuk & Daszyńska-Daszkiewicz 2018). Additionally period spacing patterns allowed Aerts et al (2017) to place the detected near-core rotation rates into an evolutionary sequence, with the aim to remedy shortcomings in angular momentum transport inside stars.…”
Section: Introductionmentioning
confidence: 99%